Design and Preliminary Results of Matching Network for MW Scale High Current RF Ion Source. (3rd October 2017) - Jiang, Caichao; Hu, Chundong; Xie, Yahong; Xu, Yongjian; Chen, Shiyong; Cui, Qinglong; Zhao, Yuanzhe; Xie, Yuanlai
Abstract: The RF ion source is the most promising ion source, which can be operated with steady state. When the Radio Frequency (RF) ion source works, the key point is how to transmit and couple the RF power to the plasma with the RF power transmission unit. In this technical note, the principle of RF matching network was analyzed and designed. The RF power transmission unit was tested on RF ion source test bed. Based on the experimental data, the function of each components of impedance-matching network is analyzed and optimized. The results show that matching network can keep high RF coupling efficiency with variable plasma parameters and decreases the reflected RF power.